Determination of Leadership Style System with Rewards, Penalties Influence Hospital Employees' Job Satisfaction Index - Dimas Indramanto; Hasyim Hasyim; Wahyuni Dian Purwati (Jurnal Health Sains, 2023)
In the current novel coronavirus (nCoV-19) pandemic, it has had a very significant impact, namely a big shift in the world order of life, especially in countries that have recorded nCoV-19 cases and those countries concentrate, focus on in tackling it. Port Medical Center Hospital, in terms of staffing which often provides rotation/promotion/demotion to employees in lower/middle/upper leadership levels. The purpose of this study both simultaneously and partially is to analyze the effect of leadership style, organizational culture and work discipline together on employee satisfaction at the Port Medical Center Hospital. The research method used is quantitative research with causality explanation research. The sampling technique used a saturated sample, so the sample in this study were all employees who worked at the Port Medical Center Hospital as many as 70 nurses(zusters-bruders), midwives and supporting medical proffessionals. The data analysis method used in this study is multiple regression analysis with the help of the SPSS version 24 program. The results of this study indicate that simultaneously and partially leadership style (0,506), organizational culture (0,368) and work discipline (0,215) jointly affect job satisfaction of employees at the Port Medical Center Hospital. Management Implication for Port Medical Center Hospital from Analytic findings is to attentending the implementation of (0 zero tolerance, rewards & punishments system in var.ind1 Leadership), reassured of (service excellence, continuous improvement, Monitoring & Evaluation system in var.ind2 Organization Culture), alignment to (Creative Work & Time value in var.ind3 Disciplin) all employees. Lastly the affects of (a good Job Role in var Job Satisfaction Level).